INVESTMENT RESOURCESOF NON-STATE PENSIONS FUNDS: NATURE AND ESPECIALLY THE FORMATION (Socio-economic relations in the digital society, 2019)
It is analyzed and summarized existing economic literature approaches to the interpretation of the investment resources. Built structural and logical scheme of formation and use of investment resources of non-state pension fund. An author’s vision of the nature of the investment resources in the context of non-state pension fund is offered. Under the investment resources of non-state pension funds understand the author proposes a set of pension savings on individual pension accounts of the fund generated by pension contributions of investors, and investment income (loss) from their accommodation in pension assets. The proposed definition of investment resources NPF, first, emphasizes the purpose of the  funds, and it states that a “retirement savings”, ie the funds intended for the payment of pensions; secondly, through the explanation of pension funds as an aggregate pension savings on individual pension accounts fund participants revealed who the owners of such funds; Thirdly, delineated sources of retirement funds (pension contributions of depositors and investment income (loss) from their accommodation in pension assets). The specific features of the investment resources of non-state pension funds is their cash, use for financial investment, long-term investment horizon, certainty in terms of investment and so on.
Keywords: investment resources; non-state pension fund; pension contributions; investment activity